Delay Mitigation in the Malaysian Housing Industry: A Structural Equation Modelling Approach - Chang , Saar Chai; Yusof, Aminah Md; Habil, Hadina (Penerbit Universiti Sains Malaysia, 2015)
The housing industry is one of the major contributors to the economy in Malaysia due to the constantly high housing demand. The housing demand has increased due to the rapid growth in population and urbanisation in the country. One of the major challenges in the housing industry is the late delivery of housing supply, which in some instances leads to sick and abandoned housing projects. Despite being extensively investigated, this delay is still a common phenomenon of the housing industry in Malaysia. As delay in delivery could result in a negative impact, there is a strong need to review the housing delay mitigation measures practised in Malaysia. This paper aims to evaluate the current delay mitigation measures and its main objective is to explore the relationship between the mitigation measures and delay in housing via a Structural Equation Modelling (SEM) approach. A questionnaire survey through an online survey tool was conducted across 13 states and three Federal Territories in Malaysia. The target respondents are the local authorities, developers, consultants (principal submitting persons) and contractors. The findings show that 17 mitigation criteria can be extracted using principal component analysis. These measures were categorised as predictive, preventive, organisational or corrective. This paper demonstrates that preventive measures are the most influential mitigation measures for housing delivery delay